Reduced cerebral cortical but elevated striatal concentration of somatostatin-like immunoreactivity in dominantly inherited olivopontocerebellar atrophy. - Kish, S J (1993)
Somatostatin-like immunoreactivity (SLI) was measured in the brains of nine patients with dominantly inherited olivopontocerebellar atrophy (OPCA), who all had a marked deficit of the cholinergic marker choline-acetyltransferase (ChAT) in the cerebral cortex and striatum. Mean concentrations of SLI in OPCA were significantly reduced by 42-58% in parietal and occipital cortices and frontal cortical eye fields, but were normal in other cortical areas, including two subdivisions of the temporal cortex which show marked depletions of both SLI and ChAT in Alzheimer's disease. This dissociation of SLI and ChAT indicates that a cortical cholinergic deficit does not invariably lead to reduction of somatostatin. In the caudate nucleus, the region of OPCA brain having the most severe ChAT deficit (-81%), SLI levels were significantly elevated by 46% and were negatively and significantly correlated with ChAT activities (r = -0.66). The SLI alterations could be due to abnormal somatostatin metabolism or release, or an increased number of somatostatin-containing neurons and could contribute to the brain dysfunction of OPCA.